Evaluating the Impact of Reciprocal Teaching Strategy on International Postgraduate Science Education Programs - Alsalhi, Najeh Rajeh Alsalhi; Alqawasmi, Abdellateef Abdelhafez; Alakashee, Bushra Ahmad; Al-Qatawneh, Sami; El-Mneizel, Abdalla Falah; Al-Barakat, Ali Ahmad; Al-karasneh, Samih Mahmoud (Journal of International Students, 2024)
This paper aims to assess the impact of the reciprocal teaching strategy on the academic performance of student-teachers enrolled in the Higher Professional Diploma (HDE) program at Ajman University, United Arab Emirates. The study adopts a quasi-experimental design, employing pre- and post-tests and a control-experimental group configuration. The sample comprises 80 student-teachers selected from Ajman University during the second semester of the academic year 2022-2023. An academic achievement test in a multiple-choice format serves as the research instrument. The study’s outcomes reveal noteworthy differences, indicating significant mean variations in the post-test scores between the experimental and control groups, favoring the control group in the context of the Reciprocal Teaching strategy. These results hold implications for international students, prompting considerations about the transferability and generalizability of teaching strategies across diverse cultural and educational settings.